2013
DOI: 10.1111/jonm.12110
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of nursing tasks in medical and surgical wards

Abstract: Nurse managers should review the level of interruptions to nurses' work and ensure appropriate levels of supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 25 publications
(46 reference statements)
1
29
2
Order By: Relevance
“…This offers a different perspective on nurses' administrative work, which focuses on its relationship to the content and organization of nursing practices. Most studies are based on an idealized patient-centred model of nursing and either report on nurses' complaints about administrative work and its burdens or criticize it by emphasizing its impact on decreasing bedside nursing time (Hendrich et al 2009, Dearmon et al 2013Farquharson et al 2013, Antinhao et al 2015. This study moves beyond this frame to show that nurses' perceptions of DOA and its burdens are not necessarily linked to the time spent, but to organizational factors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This offers a different perspective on nurses' administrative work, which focuses on its relationship to the content and organization of nursing practices. Most studies are based on an idealized patient-centred model of nursing and either report on nurses' complaints about administrative work and its burdens or criticize it by emphasizing its impact on decreasing bedside nursing time (Hendrich et al 2009, Dearmon et al 2013Farquharson et al 2013, Antinhao et al 2015. This study moves beyond this frame to show that nurses' perceptions of DOA and its burdens are not necessarily linked to the time spent, but to organizational factors.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, several authors demonstrate that the time spent on documentation is internationally proportionate: 10% of nurses’ time is spent doing paperwork in Britain (Farquharson et al . ), 9·3% in Greece (Kiekkas et al . ), and 13% in Australia (Fitzgerald et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature supports decreasing nursing care interruptions, a negative patient safety impact, and increased cost and risk when interruptions are experienced (Barclay, 2010;Dearmon et al, 2013;Farquharson et al, 2013;Hall et al, 2010;Hamdi et al, 2012;Unruh & Zhang, 2014). The lack of functional computers/computer carts was reported as the number one barrier to nursing care in a case study hospital (K. Peoples, Chief Nursing Officer, personal communication, January 12, 2015).…”
Section: Intended Improvementmentioning
confidence: 99%
“…As of 2012, 44% of acute care hospitals had adopted a basic electronic medical record (EMR), which was more than triple the 2009 adoption rate (Charles, King, Patel, & Furukawa, ). Maintaining functioning computers and computer equipment is essential to the nursing process, workflow, and a hospital's financial health (Dearmon et al., ; Farquharson et al., ; Hamdi, Oweis, Abu Zraiq, & Abu Sammour, ; Popescu, Currey, & Botti, ). The Agency for Healthcare Research and Quality () found for every 8‐hr shift, a nurse spends 4.5 hr charting.…”
Section: Introductionmentioning
confidence: 99%